Linear transformation shift register sequences - Ming-sheng WANG; Zai-liang TANG (网络与信息安全学报)
Linear transformation shift registers (TSR) were introduced by Tsaban and Vishne,which was a word-oriented shift register output a word per step.Some basic properties of sequences generated by the TSR were presented,and a new criterion for deciding if the characteristic polynomial of a TSR system is irreducible was given.This criterion avoids operations in extension fields.